2019
DOI: 10.3389/fped.2019.00195
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis as a Comorbid Condition in Chronic Fatigue Syndrome (CFS): Secondary Analysis of Data From a CFS Case-Control Study

Abstract: Background: Endometriosis (EM) is a recognized co-morbid condition in women with chronic fatigue syndrome (CFS). This analysis evaluates the impact of EM on the health of women with CFS by comparing selected health characteristics and laboratory parameters in women with CFS with and without EM (CFS+EM and CFS-only). Methods: This secondary analysis included all 36 women with CFS from a cross-sectional study of CFS in Wichita, KS, conducted between 2002 and 2003. The health ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…However, we also noted that asthenia was among the most frequently reported symptoms. This is in agreement with studies reporting significant comorbidity between endometriosis and fatigue/chronic fatigue syndrome (26,27) due to excessive function of the immune system as a response to continuous, silent inflammation determined by the presence of the disease (1, 2). Bladder pain was the least frequent symptom, as evidence of the lower incidence in the anterior compartment and more frequent incidence of the presence of endometriosis in the posterior compartment probably due to factors related to the embryonic origin of the disease (4,13,14).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, we also noted that asthenia was among the most frequently reported symptoms. This is in agreement with studies reporting significant comorbidity between endometriosis and fatigue/chronic fatigue syndrome (26,27) due to excessive function of the immune system as a response to continuous, silent inflammation determined by the presence of the disease (1, 2). Bladder pain was the least frequent symptom, as evidence of the lower incidence in the anterior compartment and more frequent incidence of the presence of endometriosis in the posterior compartment probably due to factors related to the embryonic origin of the disease (4,13,14).…”
Section: Discussionsupporting
confidence: 92%
“…It is well known that stress affects the physiology of the pelvic organs and disturbs the hypothalamic-pituitary-adrenal axis, leading to chronic, painful, and inflammatory disorders (36). The results of the negative impact of endometriosis symptoms on quality of life, work/study productivity, and personal relationships in turn cause high levels of psychological and emotional distress (26,27). The stressinflammation-pain crosstalk through the hypothalamicpituitary-adrenal axis activity indicates that stress relief should affect inflammation and, in turn, reduce pain responses (37).…”
Section: Discussionmentioning
confidence: 99%
“…The fatigue difference between men and women may be influenced by the physiological and psychological characteristics of women. First of all, women are prone to gynecological diseases, and many studies have shown that ovarian cysts, uterine fibroids, menstrual abnormalities, endometriosis, etc., are risk factors for ME/CFS ( 30 , 31 ). Second, female university students are at a higher level of the female group.…”
Section: Discussionmentioning
confidence: 99%
“…Presenteeism or “sickness presenteeism” 28 describes the situation when individuals, while ill or unwell, come to work but do not function at optimal capacity. 28 Many publications have confirmed that endometriosis is a debilitating condition, 13 frequently associated with absenteeism, 2932 high levels of comorbidity, 3335 presenteeism 24 and high financial burden due to overlapping costs of treatment and absence from work. Thus, it is thought that there is a relationship between the high value for presenteeism for endometriosis, the high financial burden associated with diagnosis, management and treatment of the condition and seeking to maintain job security to mitigate additional financial distress.…”
Section: Discussionmentioning
confidence: 99%
“…Fraser et al, 41 after investigating the impact of heavy menstrual bleeding on a population of women in Europe in over 12 months, reported approximately half of the respondents “experienced unusual high levels of fatigue tiredness or exhaustion which was directly attributed to the heavy menstrual bleeding” and 20% of women indicated this tiredness affected their daily activities. Recent work has outlined a relationship between endometriosis and chronic fatigue syndrome, 34,35 particularly as endometriosis is associated with increased levels of inflammation 4244 and other immunologic conditions such as asthma and allergies. 35,45,46 These results along with those of the current study underscore the need for further research into fatigue related to gynecological disorders, as there is relatively little literature about this as a symptom and its impact.…”
Section: Discussionmentioning
confidence: 99%